Defining and identifying a loading basis for the full-field reconstruction of plate structures under tension loads - Martini, Dominique; Hochard, Christian; Charles, Jean-Paul (European Journal of Computational Mechanics, 2012)
This method defines a loading basis for plate structures which is identified from strain measurements in order to reconstruct the mechanical fields. This loading basis is given by the decomposition of a global structure into simple substructures associated with the loaded boundaries only. Some elementary bases are defined for each substructure depending on its local edge effect. A global basis is then obtained by the equilibrium of the complete structure. The main advantage of this approach is to classify the basis vectors depending on their influence on the overall response of the structure.